2020
DOI: 10.25004/ijpsdr.2020.120608
|View full text |Cite
|
Sign up to set email alerts
|

Production of value added Oyster mushrooms

Abstract: Mushrooms are ironic in nutrimental resources and have converted into one of the common foods in the previous twenty years globally. The types of edible mushrooms are button, milky and oyster mushrooms. The research aimed at value addition of Oyster mushrooms by rising on paddy substrate complemented with two concentrations of four different medicinal plants. The plant parts selected were flowers of Butea monosperma, leaves of Moringa olifera, bark of Cinnamonom zeylianicum, fruits of Corindraum sativum at 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The result showed that maximum percentage of inhibition was observed in T3 -Cuminum cyminum (jeera) (98.24%) followed by T4-Mentha spicata (pudina) (97.54%), T2-Coriandrum sativum (coriander) (92.57%), T1 -Allium sativum (garlic) (82.16%) and T0-control [Agaricus bisporus (alone)] (0.00%) (Table 3). [21] reported that fruits of Coriandraum sativum at 5 and 10% concentration produced more mushroom, but the growth was slow. Jahan et al [22] found that botanicals like garlic and henna reduced the radial colony diameter of pathogen appreciably at different concentrations.…”
Section: In Vitro Effect Of Botanicals On Radial Growth (Mm) and Perc...mentioning
confidence: 99%
“…The result showed that maximum percentage of inhibition was observed in T3 -Cuminum cyminum (jeera) (98.24%) followed by T4-Mentha spicata (pudina) (97.54%), T2-Coriandrum sativum (coriander) (92.57%), T1 -Allium sativum (garlic) (82.16%) and T0-control [Agaricus bisporus (alone)] (0.00%) (Table 3). [21] reported that fruits of Coriandraum sativum at 5 and 10% concentration produced more mushroom, but the growth was slow. Jahan et al [22] found that botanicals like garlic and henna reduced the radial colony diameter of pathogen appreciably at different concentrations.…”
Section: In Vitro Effect Of Botanicals On Radial Growth (Mm) and Perc...mentioning
confidence: 99%